The role of low and high spatial frequencies in exogenous attention to biologically salient stimuli. - Luis Carretié (Public Library of Science (PLoS), 2012)
Exogenous attention can be understood as an adaptive tool that permits the detection and processing of biologically salient events even when the individual is engaged in a resource-consuming task. Indirect data suggest that the spatial frequency of stimulation may be a crucial element in this process. Behavioral and neural data (both functional and structural) were analyzed for 36 participants engaged in a digit categorization task in which distracters were presented. Distracters were biologically salient or anodyne images, and had three spatial frequency formats: intact, low spatial frequencies only, and high spatial frequencies only. Behavior confirmed enhanced exogenous attention to biologically salient distracters. The activity in the right and left intraparietal sulci and the right middle frontal gyrus was associated with this behavioral pattern and was greater in response to salient than to neutral distracters, the three areas presenting strong correlations to each other. Importantly, the enhanced response of this network to biologically salient distracters with respect to neutral distracters relied on low spatial frequencies to a significantly greater extent than on high spatial frequencies. Structural analyses suggested the involvement of internal capsule, superior longitudinal fasciculus and corpus callosum in this network. Results confirm that exogenous attention is preferentially captured by biologically salient information, and suggest that the architecture and function underlying this process are low spatial frequency-biased.